2019
DOI: 10.1039/c9qo01028a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silacyclopent-2-en-4-ols via intramolecular [2 + 2] photocycloaddition of benzoyl(allyl)silanes

Abstract: Organosilicon compounds are versatile units with a wide range of uses from medicinal chemistry to the field of organic electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In 2019, the Afonso and Candeias group reported a unique synthesis of silacyclopentanols using cinnamyl silane substrates 1m , in which the cyclization mode mimics the UV-initiated Paternò–Büchi type [2 + 2] cycloaddition (Scheme 19). 37 It is noteworthy that light irradiation did not initiate the formation of highly reactive siloxycarbenes. Instead, CO activation occurred selectively, enabling [2 + 2] cycloaddition upon reaction with alkenes.…”
Section: Photo-induced Reactions With Siloxycarbenes As Key Intermedi...mentioning
confidence: 97%
“…In 2019, the Afonso and Candeias group reported a unique synthesis of silacyclopentanols using cinnamyl silane substrates 1m , in which the cyclization mode mimics the UV-initiated Paternò–Büchi type [2 + 2] cycloaddition (Scheme 19). 37 It is noteworthy that light irradiation did not initiate the formation of highly reactive siloxycarbenes. Instead, CO activation occurred selectively, enabling [2 + 2] cycloaddition upon reaction with alkenes.…”
Section: Photo-induced Reactions With Siloxycarbenes As Key Intermedi...mentioning
confidence: 97%
“…In 2019, Candelais et al. reported an intramolecular PB reaction using 419 nm light in which the carbonyl part is an acylsilane 55 [46] . The bicyclic product 56 was observed by NMR, but was unstable to silica gel column chromatography, yielding the silylacycle 57 together with other by‐products.…”
Section: [2+2]‐heterocycloadditions Via Direct Irradiation Of the Car...mentioning
confidence: 99%
“…In 2019, Candelais et al reported an intramolecular PB reaction using 419 nm light in which the carbonyl part is an acylsilane 55. [46] The bicyclic product 56 was observed by NMR, but was unstable to silica gel column chromatography, yielding the silylacycle 57 together with other by-products. By treatment with a 10 % NaHSO 4 aqueous solution, the authors could convert quantitatively and selectively 56 to the silylacyclopentene 57, triggering the formation of different five-membered silylacycles (Scheme 11).…”
Section: Other Examples: O-containing Four-membered Cycles As Interme...mentioning
confidence: 99%
“…Following the general procedure, 3a was obtained in 66% yield (29.5 mg) as an off-white amorphous solid. 23 (8). Cyclopentene 3b (20 mg, 40 μmol) was dissolved in dry ACN (2 mL) in an oven-dried round-bottom flask under an argon atmosphere.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Activated alkynes have been shown to undergo slow inter- and intramolecular cyclopropenations following ring collapse to give β-silylated enones (Scheme ), , while ambiphilic donor–acceptor carbenes derived from trifluoroacetylsilanes were recently explored. , Concerning olefins, only the highly electron-withdrawing dialkyl fumarate and maleate have been reported to undergo cyclopropanation, , yielding cyclopropyl silyl ethers that are prone to ring opening through hydrolysis and are therefore not synthetically useful for cyclopropane synthesis. Despite the preference for acylsilane carbonyl to react in a [2+2]-photocycloaddition reaction, , singlet nucleophilic carbenes with tethered olefins were recently shown to undergo rapid [2+1]-cycloaddition . All in all, formal cyclopropanation of olefins with acylsilane-derived carbenes remains poorly explored due to the required presence of electron-withdrawing groups in the olefin which renders instability to the resulting silyl ether cyclopropanes.…”
Section: Introductionmentioning
confidence: 99%